Archival solution API to upload bulk file and managing the data in cloud storage. (19th August 2020) - Padhy, Neelamadhab; Mishra, Raman Kumar; Mishra, Samaresh
The application programming interface (API) as a means of communication to establish a connection with the cloud, which allows storing the vast amounts of heterogeneous data. Data has been steadily growing over the past several years. Software developers can use different data from cloud as convenient ecosystems for developing, deploying, testing and maintaining their software. API provides the archival solution and storing the data in the cloud. This platform also plays an essential role in managing them effectively with improved transfer rates. API is becoming increasingly dynamic and complex day by day. One of the significant challenges faced by us is to develop appropriate individual API and extensible mechanisms for managing and storing the data in the cloud. The objective of this paper is to utilize the storage efficiently based on API capability and analysis of (extreme amounts of) raw heterogeneous data.